PENGATURAN SUAP DI SEKTOR SWASTA SEBAGAI TINDAK PIDANA KORUPSI DI INDONESIA - Rizki Wijayanti; Yuliati; Prija Djatmika (Klausula, 2024)
This article aims to explore the qualification of bribery in the private sector as a criminal offense in Indonesia, as there is currently no specific positive legal regulation capable of prosecuting individuals involved in private sector bribery, resulting in a legal vacuum. The use of criminal law must consider the realization of a just and prosperous society, and the costs of criminalizing such acts (bribery in the private sector) should be balanced with the outcomes to be achieved. Although Indonesia's Law on the Eradication of Corruption (Law No. 31 of 1999, as amended by Law No. 20 of 2001) lags behind and is not in line with the United Nations Convention against Corruption (UNCAC), Indonesia should align its national criminal law with UNCAC, particularly Article 21 of UNCAC. By introducing new concepts and formulating provisions regarding bribery in the private sector in the Law on the Eradication of Corruption, as well as implementing the Deferred Prosecution Agreement (DPA), it is hoped that future cases of bribery in the private sectorin Indonesia can be effectively addressed.